INOVASI PENGELOLAAN HAMA TERPADU LALAT BUAH PADA PERTANAMAN JERUK DI DAERAH SUNGKAI KECAMATAN PAUH KOTA PADANG - Hidrayani Hidrayani; Zahlul Ikhsan (LPPM Universitas Andalas, 2021)
Orange is one of the horticultural commodities that deserve to be developed because it can be used as a good source of income for farmers. Efforts to increase the production of citrus plants cannot be separated from the problem of pest, which results in decreased production. Fruit flies are the most important pests that interfere with the production of citrus cultivation in Sungkai. Extension activities and monitoring of integrated pest management of fruit flies in citrus plantations in the Sungkai area of Padang City. The method applied in the extension of integrated pest management (IPM) for fruit flies is through training and Focus Group Discussions and making pilot demonstration plots. Participants in fruit flies' integrated pest management counseling activity are members of the P4S Sungkai Permai, Sungkai Permai Farmers Group, Bukik Bulek, and Pulau Indah, and all communities in the Sungkai area. The IPM technique used to reduce fruit fly pests in Sungkai is land clearing (sanitation). Prevention of fruit fly pests with sanitation has the advantage of low operating costs and low impact or hazard to worker health and the environment. Cleaning the remains of these plants means that we break the life cycle of pests, thereby reducing the pest population. Through this counseling, farmers know and understand how to implement land sanitation to control fruit fly pests. In addition, citrus farmers in Sungkai also have field demonstration plots of land sanitation techniques for citrus plantations to reduce fruit fly pests.